The Effect of Transfer Pricing, Tunneling Incentive, Thin Capitalization, and Capital Intensity against Tax Avoidance - Bianca Mutiara Putri; Einde Evana (Borong Newinera Publisher, 2024)
This study aims to investigate the influence of transfer pricing, tunneling incentives, thin capitalization, and capital intensity on tax avoidance practices in mining companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2022. The context of this study lies in the complexity of global taxation and increasing concerns over tax avoidance practices that have prompted the need for a deeper understanding of the factors influencing corporate behavior in this regard. The research method employed involves the use of statistical regression to measure the relationship between these variables. The analysis results show that tunneling incentives have a significantly negative effect on tax avoidance practices, while thin capitalization and capital intensity significantly influence tax avoidance practices positively. Meanwhile, transfer pricing does not have a significant effect on tax avoidance practices. These findings suggest that tax avoidance practices tend to be carried out by companies employing thin capital structures and having significant business activities to invest their assets in fixed assets. In this context, the study provides valuable insights for regulators and practitioners in designing policies aimed at reducing tax avoidance practices. By understanding the factors influencing the company's decision in this regard, more effective prevention and control measures can be implemented. In conclusion, this study emphasizes the importance of paying attention to the interaction between transfer pricing, tunneling incentives, thin capitalization, and capital intensity in the context of corporate tax avoidance to develop a holistic and effective policy approach.